Incentives for the promotion of timber construction: Study in three European countries - Bregen, Janina (Karelia University of Applied Sciences, 2023)
This publication presents the results of thesis work conducted by Janina Bregen from Jade UAS, Oldenburg, Germany. The work includes research findings from her internship at Karelia UAS for the "Sustainable Building Technologies- Community of Practice" (SBTCP) project, which led to her bachelor thesis work on analyzing incentives and barriers of timber construction in Austria, Finland, and Germany. The idea was to conduct a literature review on the selected topic to formulate questions for expert interviews to identify and rank the incentives and barriers for each context. 13 professionals with experiences in timber or concrete construction took part in the interviewing sessions. The interviews were partly online and some of the interviews were conducted in person in Finland. The responses were collected and compiled to formulate the resultant list of incentives for timber construction in three European countries. The SBTCP project by Karelia UAS in collaboration with Salzburg UAS and Jade UAS aims to enhance the sustainable development of timber construction through using advanced expertise and technologies.